SIU-ICUD: Localized Prostate Cancer: Pathological Factors That Influence Outcomes and Management - Gladell P. Paner; Eva M. Compérat; Samson W. Fine; James G. Kench; Glen Kristiansen; Rajal B. Shah; Steven Christopher Smith; John R. Srigley; Geert J. L. H. van Leenders; Murali Varma; Ming Zhou; Mahul B. Amin (Société Internationale d’Urologie Journal, 2025)
Background/Objectives: Pathological factors are integral in the risk stratification and management of localized prostate cancer. In recent years, there has been an upsurge of studies that uncovered novel approaches and have refined prognostic factors for prostate cancer in needle biopsy and radical prostatectomy (RP) specimens. Methods: We conducted a review of literature and summarized the significant recent updates on pathological factors for localized prostate cancer. Results: Innovative factors derived from the traditional Gleason grading, such as the extent of Gleason pattern 4 and presence of cribriform pattern are now recognized to significantly improve discrimination of outcome. The components and rules of Gleason grading themselves underwent modifications, and the subsequent prognostic grouping of the different grades (Grade group) have resulted in enhanced stratification of behavior more meaningful in management decision. The approaches for grade reporting in systematic or targeted needle biopsies and in RP with multifocal cancers are also being optimized. Newer tumor growth pattern-based factors such as intraductal carcinoma and atypical intraductal proliferation can have ramifications in management, especially in the background of low to intermediate risk prostate cancers. Gleason grade considerations in the different post-treatment settings and for de novo and residual prostate cancers with varying treatment effects have also been explicated. Likewise, the application of more traditional factors in tumor extent and perineural invasion in biopsy, or positive surgical margin in RP, have also evolved. Conclusions: Some of these newer pathological factors are now officially recommended in standardized pathology reporting protocols and are applied in the management decision for localized prostate cancer.